1977
DOI: 10.1103/physrevlett.38.541
|View full text |Cite
|
Sign up to set email alerts
|

Self-Generated Magnetic Fields in the Microwave Plasma Resonant Interaction

Abstract: The laser plasma interaction is simulated by the interaction of a microwave beam with an inhomogeneous, collisionless plasma. Magnetic fields are generated perpendicular to the density gradient and to the incident-wave polarization. The observed sharp reversal of field direction in the resonant region supports resonant absorption as the generation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(5 citation statements)
references
References 8 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…This result is well known in plasma physics and electrodynamics of continuous media as the inverse Faraday effect The corresponding steady magnetic field generated by waves in plasma are observed in experiments via the optical Faraday rotation and other methods [76][77][78].…”
Section: Direct Electric Current and Magnetization Associated With Th...mentioning
confidence: 65%
“…This result is well known in plasma physics and electrodynamics of continuous media as the inverse Faraday effect The corresponding steady magnetic field generated by waves in plasma are observed in experiments via the optical Faraday rotation and other methods [76][77][78].…”
Section: Direct Electric Current and Magnetization Associated With Th...mentioning
confidence: 65%
“…[1][2][3][4][5][6][7] Some of the observed consequences are generation of high-energy electron bunches, 1,2 excitation of temporal plasma-wave echoes in the ion wave regime, 3 excitation of ion-wave wakefield, 4 large amplitude electron plasma waves (EPW) based plasma accelerators, 5,6 and self-generation of magnetic fields. 7 The propagation of electromagnetic (em) waves through temporally growing plasmas has also been analyzed, mainly in theory, [8][9][10] including the study of dynamic behavior of microwaves through a gaseous medium that get ionized in the incident wave field. 10 It is shown that the waves can propagate through plasmas that are overdense in the steadystate approximation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In addition to these non-linear phenomena, the relativistic ponderomotive force and the relativistic mass reveal in the interaction between intense MW and plasma. A number of non-linear phenomena appear during this interaction, including resonance absorption, frequency upshift, charged particle acceleration, and high-energy super-thermal electron generation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of non-linear phenomena appear during this interaction, including resonance absorption, frequency upshift, charged particle acceleration, and high-energy super-thermal electron generation. [1][2][3][4][5][6][7][8][9] In addition to these non-linear phenomena, the relativistic ponderomotive force and the relativistic mass reveal in the interaction between intense MW and plasma. These two non-linear effects arise when the intensity of the MW beam is sufficiently high.…”
Section: Introductionmentioning
confidence: 99%